SOCIAL MEDIA EFFECTS MAKE POPULAR NEW TRAVEL DESTINATIONS: COUNTRY ABOVE CLOUDS - Sonny Indrajaya (Proceeding of The International Conference on Economics and Business, 2022)
Tourism is a travel activity carried out temporarily from the original residence to the destination area with the reason not to settle or make a living but only to fulfill curiosity, spend leisure or holiday and other destinations. One of the new tourism destinations that has a natural charm as if we are standing on a bumpy cloud. This new tourism destination is named after the country above the clouds located in Lebak Regency, Banten, Indonesia. The results of this study the role of social media marketing can introduce and popularize the country's tourism above the clouds located in the district of Lebak, Lebak and can affect the image of tourists about the quality of the destination and can also provide satisfaction and loyalty to tourists.